Pengenalan Batik Jumputan Sebagai Media Alternatif Keterampilan Kepada Ibu PKK Perum Solo Elok, Mojosongo, Surakarta - FP Sri Wuryani; Rahel Olivia Chandra Estoni Putri (Institut Seni Indonesia Surakarta, 2022)
ABSTRACTWomen from low-income families encounter some challenges because of their gender status. Thus, attention is required to improve women’s engagement in the socioeconomic development process, a program implemented by the government in the scope of women’s welfare. However, the program’s impact on women has not been totally positive. Providing training related to Jumputan (tie-dye) batik making is one of the alternatives for women empowerment, particularly among local housewives community (PKK) members in Perum Solo Elok, Mojosongo, Surakarta. Batik is a method of decorating cloth with dye techniques; however, in the majority of Indonesian society, the term batik refers to batik-patterned textiles or printed batik rather than actual batik. This course is intended to support attempts to preserve traditional art, particularly batik artworks. Activities are carried out in collaboration with program partners PKK Perum Solo Elok, Mojosongo, Surakarta. The approach used to carry out this introductory activity prioritizes participant and mentor activeness, which is supported by the use of media and effective and efficient training models, with the goal of training materials being well accepted by trainees, who are PKK members. In accordance with this, the program design, particularly this creative workshop, refers to David Gibson’s concept of design phases divided into three broad groups: planning, design, and implementation. The stages of activity implementation include three methods: mutual approach, personal approach, and partnership approach. This skill is to add a variety of skills to partners in order to develop a hobby and business related to tie-dye batik.